The role of marine salt and surfactants in the decline of tyrrhenian coastal vegetation in Italy (Annales des Sciences Forestières, 1995)
The decline of coastal vegetation is a phenomenon affecting some areas of the Mediterranean region and Australia; it is due to the presence of surfactants in marine aerosols, a consequence of sea pollution by detergents. This paper gives some observations made at various sites along the Tyrrhenian coast in Italy. The authors show that the presence of surfactants in the environment correlates with the presence of sea salt, and that the impact of surfactants on vegetation is local and occurs in association with strong sea winds. The study of the synergistic effect of surfactants and sea salt on the crowns of trees exposed to aerosols suggests that the surfactant can cause direct damage, while the absorption of sea salt is enhanced by the presence of the surfactant only when exposure to aerosol is prolonged, or if it is administered in very high concentrations.